Genetic diversity analysis of Asian clam Corbicula fluminea in the Hongze Lake based on mitochondrial cytochrome b gene. (3rd April 2018) - Zhu, Chuankun; Li, Jin; Xie, Songguang; Ding, Huaiyu; Pan, Zhengjun; Wang, Hui; Chang, Guoliang
Abstract: The Asian clam Corbicula fluminea is a small bivalve with high nutritional and medical values. However, natural resources of C. fluminea have declined in many areas of China including the Hongze Lake. In this study, 119 individuals from 10 sites of this lake and 2 outgroups were analyzed using a 456 bp mitochondrial cytochrome b (cytb) gene segment. Totally, 19 polymorphic sites were detected, which defined 16 haplotypes. Polymorphism varied among the 10 populations with those at the water inlet being more polymorphic. Most FST values among these populations were below 0.15 with the overall value of 0.060 ( p < .05), meanwhile, the overall gene flow was 7.67, both of which indicated the low level of population differentiation in this lake. Neutrality test and mismatch analyses indicated that population explosion may have occurred in this lake. The results obtained in this study will provide useful information for artificial breeding and resource protection of this species in the Hongze Lake.